PENINGKATAN KEMAMPUAN MENULIS TEKS CERITA PENDEK MELALUI MEDIA LITERASI VISUAL PADA MURID KELAS IV UPT SPF LABUANG BAJI I MAKASSAR - Nur Sri Putri Mui; Dr. Andi Adam, M.Pd; Desy Ayu Andhira, S.Pd., M.Pd (STKIP Subang, 2025)
This classroom action research was conducted to improve the short story writing skills of fourth-grade students at UPT SPF Labuang Baji I Makassar through the use of visual literacy media. The problem identified was the students’ low interest and ability in writing short stories, particularly in organizing ideas and applying story elements effectively. The study aimed to examine whether visual literacy media such as images and videos can enhance students' imagination and narrative structure. The research was carried out in two cycles, each consisting of three meetings. Data were collected through observation and written tests, then analyzed descriptively and quantitatively. The results showed a significant improvement in students' writing scores: from 75.3 and 78.5 in Cycle I to 85.4 and 87.3 in Cycle II. The use of visual media helped students generate ideas more creatively and write with greater coherence. It also increased classroom engagement and students’ enthusiasm for writing activities. These findings suggest that visual literacy media can be an effective and enjoyable strategy to enhance writing skills in elementary school. Further research is recommended to explore its application to other language skills or different educational levels.